VENO2 : a generic overlay infrastructure over heterogeneous networks - Yu, Kuan (2010)
Today, the Internet has obtained an incredible success. But some aspects of the current Internet are limiting its further development to meet both current expectations as a trusted communication infrastructure and future demands for scaling to support a huge number of new users and devices. Security and IPv4/IPv6 connectivity are two mainly concerned problems among all of these aspects.